القيادة التشاركية ودورها في تحسين الآداء الوظيفي - باكة, حشاني; ليلى, سعيد; بية, غرنوق (University of eloued جامعة الوادي, 2020)
"تهدف هذه الدراسة إلى التعرف على القيادة التشاركية ودورها في تحسين الأداء الوظيفي ولدراسة هذا الموضوع طرحنا التساؤل الآتي, كيف تساهم القيادة التشاركية في تحسين الأداء الوظيفي بالمديرية العملية للاتصالات الجزائرية بالوادي وللإجابة على هذا التساؤل طرحنا جملة من الأسئلة الفرعية وللإجابة على هذه التساؤلات, اتبعنا مجموعة من الإجراءات المنهجية المتمثلة في المنهج الوصفي التحليلي واعتمدنا على الاستبيان كأداة لجمع البيانات وتوزيعه على مجتمع الدراسة المتكون من 59 عامل بالديرية العملية للاتصالات بالوادي وتم استرجاع 58 استبيان أي ما يعادل %98.30 من عدد الاستبيانات التي تم توزيعها وقد تم التحليل باستخدام البرنامج الاحصائي SPSS 25. ومن أهم النتائج التي توصلت لها هذه الدراسة هي أن تفويض السلطة يتيح للمرؤوسين فرصة الظهور والتمييز وكذا المنافسة على اكتساب المهارات من خلال استغلال الموارد المتوفرة بشكل أفضل, يزيد التفويض من تحمل المسؤولية لدى الموظفين مما يساهم في إيجاد حلول للمشكلات وتشجيع فرصة الظهور والتمييز, حيث تتيح فرصة المشاركة في اتخاذ القرار في حل المشاكل وإبداء الرأي وتخفيف العبء على القائد والعمل ضمن الجماعة يساهم في تحقيق الانسجام بين العمال والشعور بالراحة والاستقرار, فروح الجماعة تؤدي إلى ظهور التماسك كما أن التحفيز والتشجيع يزيد في تحسين الأداء وزيادة الرغبة في تحمل المسؤولية. "This study aims to identify the participatory leadership and its role in improving job performance. To explore this topic, we asked the following question: what is the role of participatory leadership in enhancing job performance in the Operational Directorate of Algerian Communications in El-Oued. The methodology represented in the descriptive analytical approach, and we relied on the questionnaire as a tool for data collection and distribution to the study population, which consisted of 59 workers in the practical district of communications in El-Oued, 58 questionnaires were retrieved, which is equivalent to 98.30% of the number of questionnaires that were distributed. The analysis has been done using the statistical program SPSS 25. One of the most significant findings of this study is that delegation of authority allows subordinates the opportunity to appear and distinguish, as well as competition to acquire skills by making better use of available resources, delegation increases the responsibility of employees, which contributes to finding solutions to problems and encouraging the opportunity to appear and distinguish, providing an opportunity Participation in decision-making in solving problems, expressing opinions, and reducing the burden on the leader. Working within the group contributes to achieving harmony among workers and a sense of comfort and stability. The spirit of the group leads to the emergence of cohesion, increases motivation and encouragement, improves performance, and increases the desire to take responsibility.
مذكرة ماستر ادارة اعمال
Keywords: القيادة ,القيادة التشاركية, الأداء, الأداء الوظيفي.; Leadership, participatory leadership, performance, job performance